Evaluation of the Epidemiological and Clinical Features of Childhood Open Globe Injuries - Demir, Ülkü (The European Research Journal, 2026)
Objectives: To determine the epidemiological and clinical characteristics of open globe injuries causing permanent visual loss in children. Methods: In our study, the files of 45 pediatric patients aged 1-18 years who were followed up in the ophthalmology clinic due to open globe injuries were retrospectively scanned. Patients’ age, gender, traumatized eye, localization of the incision, initial and final visual acuity, place of the trauma, tools causing the trauma, pathologies accompanying the trauma, surgeries after the trauma, time between the trauma and repair, and follow-up period were recorded. Results: Fifteen (33.3%) patients were female and 30 (66.6%) were male. The mean age was 10.4±4.4 years. The mean time between trauma and hospitalisation was 3.84±2.88 hours, and the mean follow-up period was 8.24±6.47 months. The right eye was traumatised in 25 (55.6%) patients and the left eye in 20 (44.4%) patients. Twenty (44.4%) patients had corneal, 18 (40%) corneascleral, and 7 (15.6%) scleral injuries. Trauma occurred at home in 31 (68.9%) patients. Penetrating injuries were detected in 39 (86.7%) patients. No rupture was observed in any patient. The most common instrument causing trauma was a knife in 14 (31.1%) patients. Conclusions: Open globe injuries were mostly observed in boys. Corneal and penetrating injuries were observed, mainly in the right eye. It was noted that most of the injuries occurred at home and with sharp objects. Our findings highlight the importance of preventive education and parental awareness to reduce the risk of ocular trauma in children.